A Systematic Review of the Antecedents and Outcomes of Career Plateau - Lediana Mareza (SENTRI: Jurnal Riset Ilmiah, 2026)
This study presents a systematic literature review on the concept of career plateau and its implications for employees and organizations. The review analyzes 29 peer-reviewed articles published between 2020 and 2025 from the Scopus database, ensuring high-quality evidence. Career plateau is identified as a multifaceted phenomenon in which individuals perceive stagnation or deadlock in their career progression, potentially affecting emotional well-being, interpersonal relationships, and professional performance. Findings indicate that antecedents of career plateau occur at multiple levels. Individual factors include personal motivation, career expectations, psychological characteristics, and emotional regulation. Job-related factors encompass role overload, work-life conflict, and limited challenge or career progression. Organizational factors involve structural limitations, ineffective career management systems, low organizational justice, and job insecurity. Protective factors, such as organizational support, positive psychological capital, continuous learning, and technology utilization—including AI—can mitigate negative consequences. Career plateau is linked to various outcomes, including increased job burnout, reduced work engagement, diminished job performance, turnover intention, and counterproductive work behaviors. However, some studies note that career plateau may also emerge as a deliberate career choice in specific contexts. The review highlights that these effects are context-dependent, influenced by sector, profession, and organizational environment. This study identifies research gaps, emphasizing the need for more rigorous empirical studies, broader sector coverage, and stronger theoretical frameworks. By synthesizing existing knowledge, the review provides a comprehensive understanding of career plateau, guiding future research and informing interventions to manage career stagnation, enhance employee well-being, and improve organizational effectiveness.